The influence of the Think Pair Share model assisted by Quizizz learning media on results studying social studies - Ahmad, Nur Hayati; Haliadi, Haliadi; Hasdin, Hasdin (PT. Riset Press International, 2024)
Education That must walk For guard sustainability life human, because without education No will There is transformation knowledge as well as social values and norms from generation old to generation young. Based on exposure the can stated that function education is a very important process and not Can free from life man. Formulation problem How application of the Think Pair Share learning model, How use of learning media interactive Quizizz, How results Study students ' eyes social studies lessons, Is There is the influence of the Think Pair Share model assisted by Quizizz learning media on results studying social studies in Class IV Cluster II Sombori Island Regency Morowali. Research purposes Analyze the influence of the Think Pair Share model assisted by Quizizz learning media on results studying social studies in Class IV Cluster II Sombori Island Regency Morowali. Types of research This is quantitative. Study quantitative can interpreted as method Research based on philosophy​ positivism, used For research on populations or sample certain. According to Sugiyono (2022) method Study experiment is method Research conducted​ with experiment, which is used For know influence variable independent ( treatment ) towards variable dependent ( result ) in controlled conditions.​ Research result Something instrument is said to be valid if instrument the can measure what it should be be measured. Validation process instrument study This carried out by expert validators.